Mittlere Tages- und Jahresgänge der Strahlungsbilanz und ihrer Komponenten über einem südwestdeutschen Kiefernwald. Eine klimatologische Interpretation - Kessler, Albrecht; Jaeger, Lutz (ERDKUNDE, 1994)
In this paper a period of fifteen years of radiation measurements is analyzed. These measurements have been carried out above a pine forest canopy in the southern part of the upper Rhine valley from 1974 to 1988. Special emphasis is given to the mean daily patterns of the months and the annual pattern of the net radiation and its components, i. e. global radiation, short-wave reflected radiation, long-wave downward radiation and long-wave emission of the forest canopy. The radiation values are related to its controlling factors namely solar radiation, air temperature, water vapour and CO2 content of the air and the cloudiness. Explaining these relationships, we use long standing records of the heat balance components: net radiation, turbulent fluxes of sensible and latent heat as well as the heat storage in stand and soil. The results are compared to a grass surface at Hamburg. The data of comparison had been recorded during the same period. As a result of this comparison we found that the annual mean of the net radiation of the grass surface is nearly half that of the forest canopy surface.